(untitled) (Journal of Nepalese Business Studies, 2006)
Today’s modern management regards human resource as the precious asset of an organization. How this important asset is treated and developed in the Nepalese business organizations is the main concern of this study. The study reveals that there is a lack of systematic approach towards human resource development in Nepalese business organizations. Most of the organizations neither have a personnel manager to look after human affairs nor allocate budget in their annual program for human resource development. This is a manifestation of low priority assigned to human resource in organizations. However, it is a good indication that some of the organizations have started to provide their employee the training though they lack clear policy framework. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.58-68